Subjek Hukum Dаlаm Ekonomі Syаrіаh - Pirdayanti, Yupi; Аbdаl (Sekolah Tinggi Agama Islam At-Tahdzib, Ngoro, Jombang, Indonesia, 2023)
This article is about the subject of law in sharia economics. The discussion of contracts studied in Sharia economic law occupies a fairly important position. A contract can be said to be valid if it has met the terms and conditions in the sharia agreement. One of the things that must be fulfilled is the contracting party. The subject of law is individual in the study of fiqh muamalah However, with the development of the times the subject of this contract is not only an individual but in the form of a legal entity. A legal entity is something based on the demands of the needs of society that by law is recognized as a supporter of rights and obligations or everything that by law can have rights and obligations. implemented in the agreements of the contribation/musyârakah more specifically on the musyarakah mu'ashirah (contemporary Sharing) contracts such as the At-Tadhamun syirkah, the Taushiyah basithah syirkah, the mas'uliah syirkah, the musahamah syirkah and the taushiyah bi al-Asham syirkah.